Pengenalan Metode Pengajaran Bahasa Arab Fun Learning di Pondok Pesantren - Nida, Nushrotun; Nurohman, Nurohman; Fatimah, Titim Siti; Azhari, Faiz; Riyadi, Agus (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Arabic language teaching in schools is still considered boring, parents' dissatisfaction with students' Arabic language skills is caused by inappropriate teaching methods. This activity aims to introduce the Fun Learning Arabic teaching method to the students of Nurul Huda Tasikmalaya Islamic boarding school. The method used in this activity is the grounded theory method. SDA conducted field observations to identify the problems of teaching methods in Nurul Huda boarding school and offered solutions by discussing the fun learning method programme. The delivery of the fun learning method teaching was carried out with a seminar or talk show model with the audience of Nurul Huda boarding school students. The results of this activity explain that the fun learning method is a solution to boring learning. In practice, there are several models of fun learning methods that can be applied in teaching Arabic, namely the hikayat (storytelling) model, ghina (singing), and takhminul lughah (guessing). The hikayat (storytelling) model in the fun learning method can be applied in teaching Arabic for maharah istima, the ghina (singing) model can be applied in teaching Arabic to memorise mufradat, and the Takhminul lughah (guessing) model can be applied in teaching Arabic for maharatul qiraah and istima'.